Contaminants at Arctic formerly used defense sites - R. J. Scrudato (19772619) (2015)
This study was conducted in order to determine if the source of contaminants at formerly used defense sites (FUDS) in Alaska were deposited as a result of military occupancy or from long-distance transport. This determination largely influences whether remediation will occur, and, if so, to what extent. For this reason, plant samples (rinsed and unrinsed) and sediment cores were collected at military and remote sites on St. Lawrence Island (SLI) and Norton Sound, Alaska during the summers of 2002, 2006, and 2007 and analyzed for persistent organic pollutants. On St. Lawrence Island sediment core samples were collected at the Northeast Cape FUDS, also a traditional fishing/hunting camp, and were sectioned and analyzed for concentrations of Polychlorinated biphenyl (PCB) congeners, Mirex, Dichlorodiphenyldichloroethylene (DDE), Hexachlorobenzene (HCB), Mercury and Cesium-137 (137Cs). Differences in the total concentrations and distributions of PCB congeners, Mirex, DDE and Mercury in sediment cores and in plants collected from the two SLI and three Norton Sound mainland formerly used defense sites indicate the majority of the contaminants found can be temporally related to releases during military occupancy and subsequent redistribution of contaminants. Contaminants in plant samples at the SLI sites are elevated relative to the two remote sites located on St. Lawrence Island and the three mainland Norton Sound FUDS at Elim, Unalakleet, and Wales. The concentrations, lateral and vertical distribution of the total PCBs, and congener-specific differences in sediments and plants readily differentiate locally derived from globally transported contaminants. The relative contaminant concentrations in sediment cores and between rinsed and unrinsed plants collected from the NEC FUDS indicate contaminants were remobilized and redistributed during recent site remediation activities. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2012.2